2020
DOI: 10.1111/vsu.13486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of computer‐assisted orthopedic surgery in horses

Abstract: ObjectiveTo describe clinical applications of computer‐assisted orthopedic surgery (CAOS) in horses with a navigation system coupled with a cone beam computed tomography unit.Study designRetrospective clinical case series.AnimalsThirteen adult horses surgically treated with CAOS.MethodsMedical records were searched for horses that underwent CAOS between 2016 and 2019. Data retrieved included signalment, diagnosis, lameness grade prior to surgery, surgical technique and complications, anesthesia and surgery tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…It is surprisingly well tolerated by the horses, likely because of speed of acquisition, low noise, and lack of movement of the gantry. It is used even more frequently for the imaging of head and neck in standing sedated horses and also for intraoperative purposes 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is surprisingly well tolerated by the horses, likely because of speed of acquisition, low noise, and lack of movement of the gantry. It is used even more frequently for the imaging of head and neck in standing sedated horses and also for intraoperative purposes 21 …”
Section: Discussionmentioning
confidence: 99%
“…It is used even more frequently for the imaging of head and neck in standing sedated horses and also for intraoperative purposes. 21 This retrospective study is based on imaging findings in clinical horses, so the findings could not be correlated with pathologic or histologic examinations, and they are not validated by a gold standard. The fact that one study group was based on suspected diagnosis may have induced a bias, and the results may also have been affected by the fact that the acquisitions were not evaluated in a blinded manner.…”
Section: Discussionmentioning
confidence: 99%
“…These features make it an ideal tool for CAOS applications in horses. The authors have gained considerable first hand expertise with this technology at their veterinary teaching hospital 16 . The manufacturer of the surgical navigation system used in the present study demonstrated a positional accuracy with a mean error ≤ 2 mm 17 .…”
Section: Introductionmentioning
confidence: 80%
“…In this retrospective study Mathieu de Preux and colleagues in Switzerland described clinical applications of computer‐ assisted orthopaedic surgery (CAOS) in horses with a navigation system coupled with a cone beam computed tomography unit.…”
Section: Computer‐assisted Orthopaedic Surgerymentioning
confidence: 99%